2016
DOI: 10.1007/s00246-016-1437-0
|View full text |Cite
|
Sign up to set email alerts
|

Late Outcome and Predictors of Adverse Events Related to the Implantation of a Permanent Pacemaker in Patients with Isolated Congenital Atrioventricular Block

Abstract: Isolated congenital atrioventricular block (ICAVB) is a rare, and pacemaker implantation is the only effective treatment. We sought to identify the predictive factors of adverse events related to pacemaker implantation in ICAVB. This is a cohort study of patients diagnosed with ICAVB who underwent pacemaker implantation from 1980 to 2014 in a single center. During the studied period, a total of 647 patients underwent implantation of their first permanent cardiac pacemaker before 30 years of age. Of these, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…If these complications are not treated in a timely manner, the treatment efficacy and prognosis of PPI in patients might be affected, along with the progression of the disease. Therefore, PPI complications have become a focus of research among cardiovascular physicians (12,13). Relevant data have previously shown that the postoperative complication rate of patients with PPI is approximately 8.2-17.4%.…”
Section: Discussionmentioning
confidence: 99%
“…If these complications are not treated in a timely manner, the treatment efficacy and prognosis of PPI in patients might be affected, along with the progression of the disease. Therefore, PPI complications have become a focus of research among cardiovascular physicians (12,13). Relevant data have previously shown that the postoperative complication rate of patients with PPI is approximately 8.2-17.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the patient's age is an aggravating factor for sudden death, since the risk of sustained ventricular tachycardia increases from 0.2% to 0.5% per year in operated and followed-up patients after 21 and 30 years old, respectively 7,8 . Some atrial arrhythmias, such as fibrillation and atrial flutter, are associated with a greater chance of death, predisposing to more severe ventricular arrhythmias 9 . Other mechanisms of sudden death result from anatomical changes that can cause hemodynamic impairment, embolism, myocardial infarction, or rupture of an aneurysm 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors for sudden cardiac death that are considered in patients with TOF are left systolic ventricular dysfunction, presyncope, syncope, palpitations, QRS duration equals to or greater than 180 ms, non-sustained ventricular tachycardia, and induction of ventricular arrhythmias in an electrophysiological study (EPS) 11 . To mitigate sudden death, the induction of sustained ventricular tachyarrhythmias in EPS becomes an important tool in stratifying patients with these risk factors in the decision to implant a cardiac defibrillator 9 .…”
Section: Introductionmentioning
confidence: 99%